Stability Analysis of Fuzzy-Model-Based Control Systems Linear-Matrix-Inequality Approach - Lam, Hak-Keung.; Leung, Allen; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2010)
In this book, the state-of-the-art fuzzy-model-based (FMB) based control approaches are covered. A comprehensive review about the stability analysis of type-1 and type-2 FMB control systems using the Lyapunov-based approach is given, presenting a clear picture to researchers who would like to work on this field. A wide variety of continuous-time nonlinear control systems such as state-feedback, switching, time-delay and sampled-data FMB control systems, are covered. In short, this book summarizes the recent contributions of the authors on the stability analysis of the FMB control systems. It discusses advanced stability analysis techniques for various FMB control systems, and founds a concrete theoretical basis to support the investigation of FMB control systems at the research level. The analysis results of this book offer various mathematical approaches to designing stable and well-performed FMB control systems. Furthermore, the results widen the applicability of the FMB control approach and help put the fuzzy controller in practice. A wide range of advanced analytical and mathematical analysis techniques will be employed to investigate the system stability and performance of FMB-based control systems in a rigorous manner. Detailed analysis and derivation steps are given to enhance the readability, enabling the readers who are unfamiliar with the FMB control systems to follow the materials easily. Simulation examples, with figures and plots of system responses, are given to demonstrate the effectiveness of the proposed FMB control approaches.
1 Introduction -- 2 Stability and Performance Conditions for MFSI State-Feedback FMB Control Systems -- 3 Stability Analysis of FMB Control Systems under MFSD Approach -- 4 BMI Stability Conditions for FMB Control Systems -- 5 Stability Analysis of FMB Control Systems Using PDLF -- 6 Regional Switching FMB Control Systems -- 7 Fuzzy Combined Controller for Nonlinear Systems -- 8 Time-Delay FMB Control Systems -- 9 Sampled-Data FMB Model Reference Control Systems -- 10 IT2 FMB Control Systems.
Keywords: Artificial intelligence; Control engineering; Computational intelligence; Artificial Intelligence; Control and Systems Theory; Computational Intelligence